Ocular Disease Profile of Rohingya Refugees Seeking Tertiary Care - Tanzin, Tanuja; Alam, Md Shahriar; Hossain, Mohammed Anwar; Haque, Mohammedul; Sen, Utpal (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: The enormous numbers of Rohingya refugees have limited access to healthcare facilities, resulting in higher health risks as well as ocular morbidity. A tertiary hospital can provide better care for ocular conditions that cannot be managed by primary care. Chittagong Medical College Hospital (CMCH) serves as the largest tertiary care facility for the southeastern region of Bangladesh by United Nations High Commissioner for Refugees (UNHCR). The study was aimed to determine the ocular diseases profile of Rohingya refugees seeking tertiary care admitted into Ophthalmology Department, CMCH. Materials and methods: Retrospective study on ocular diseases of Rohingya Refugees (n=207) over a period of 5 years from 1st September, 2017 to 31st August, 2022. Results: Out of 207 Rohingya Refugees, 59% were males and 41% were females with a ratio of 1:1.4. The highest patients were found in the age group 20-29 years (29.5%); the mean age was 21.31 (±15.631) years (Range: 0-80). Ocular trauma was found as the most common eye disease among our study population (47.3%) followed by orbital cellulitis (6.8%), glaucoma (5.8%), corneal opacity (4.3%) and corneal ulcer (4.3%). The most patients presenting visual acuity were <1/60-Perception of light (46.9%). A total of 33 (15.9%) cases had no light perception during admission. Conclusion: The primary health care providers can work on to create awareness among the Rohingya refugees on ocular diseases, help them to remove the social barriers and taboos. So that definite and timely interventions will save their vision. JCMCTA 2023 ; 34 (1) : 31-35